Twenty-First Century Gateways : Immigrant Incorporation in Suburban America - Brettell, Caroline; Hardwick, Susan Wiley; Singer, Audrey (Book collections on Project MUSE., 2008)
"Focuses on the fastest-growing immigrant populations among "second-tier" metropolitan areas. Examines the changes wrought by these new suburban settlement patterns and provides comparative analysis of immigration trends and local policy responses in these gateways. Case examples explore the challenges of newcomer integration, as well as immigration's impact on suburban infrastructure"--Provided by publisher